2010
DOI: 10.1097/acm.0b013e3181d85a4e
|View full text |Cite
|
Sign up to set email alerts
|

The Processes and Dimensions of Informed Self-Assessment: A Conceptual Model

Abstract: Central challenges to informing self-assessment are the dynamic interrelationships and underlying tensions among the components comprising self-assessment. Realizing this increases understanding of why self-assessment accuracy seems frequently unreliable. Findings suggest the need for attention to the varied influencing conditions and inherent tensions to progress in understanding self-assessment, how it is informed, and its role in self-directed learning and professional self-regulation. Informed self-assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
213
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 275 publications
(231 citation statements)
references
References 37 publications
8
213
0
2
Order By: Relevance
“…If we are to better understand the processes involved in self-assessment, greater attention needs to be placed on "the varied influencing conditions and inherent tensions to progress in understanding self-assessment, how it is informed, and its role in self-directed learning and professional self-regulation" (Sargeant et al, 2010(Sargeant et al, , p. 1212. This requires consideration of cognitive and affective aspects of self-monitoring and regulation (Ruiz-Primo, 2011).…”
Section: Core Themesmentioning
confidence: 99%
“…If we are to better understand the processes involved in self-assessment, greater attention needs to be placed on "the varied influencing conditions and inherent tensions to progress in understanding self-assessment, how it is informed, and its role in self-directed learning and professional self-regulation" (Sargeant et al, 2010(Sargeant et al, , p. 1212. This requires consideration of cognitive and affective aspects of self-monitoring and regulation (Ruiz-Primo, 2011).…”
Section: Core Themesmentioning
confidence: 99%
“…Without feedback, learners may be unclear as to how well or how poorly they are performing, and the most expedient actions they should undertake for improvement (Rees & Shepherd 2005). Self-assessment alone is unreliable; and feedback from external sources is essential to confirm or disconfirm self-perceptions (Archer 2010;Sargeant et al 2010Sargeant et al , 2011. Residents are in the process of developing self-assessment and self-monitoring skills that will serve them throughout their professional lives and feedback enables this process.…”
Section: Introductionmentioning
confidence: 99%
“…Further, self-assessment is a situationally bound cognitive process that is context specific and dependent on expertise. More recently, a study (Sargeant et al 2010) of undergraduates, postgraduate trainees, and practicing physicians found that self-assessment was informed by dynamic and fluid processes in which data from external and internal sources were interpreted. When physicians interpret their data, they may accept, reject, ignore,…”
Section: Introductionmentioning
confidence: 99%